Heat transfer enhancement of thermoelectric cooling module with nanofluid and ferrofluid as base fluids. (April 2021) - Wiriyasart, S.; Suksusron, P.; Hommalee, C.; Siricharoenpanich, A.; Naphon, P.
Abstract: In this study, the thermal performance of a compact heat sink thermoelectric cooling module with water, nanofluid, and ferrofluid as the coolants is investigated experimentally. The Ti O2 nanofluid and Fe3 O4 ferrofluid were tested at concentrations of 0.005% and 0.015%, respectively. The dummy battery pack was filled with water under a constant temperature and represented as a heat load. The results reveal that the Fe3 O4 ferrofluid showed a maximum heat transfer rate 11.17% and 12.57% higher, respectively, than that of the Ti O2 nanofluid and water. The Ti O2 nanofluid and Fe3 O4 ferrofluid with a 0.015% concentration enhanced the Peltier effect by lowering the contribution of the Fourier effect of the thermoelectric cooler (TEC), decreasing the temperature difference of the TEC cooling module by 4.6% and 9.6%, respectively, which decreases the thermal resistance of the heat sink by 7% and 14%, respectively. More importantly, the use of nanofluids and ferrofluids with a 0.015% concentration as coolants increased the pressure drop significantly, by 0.5 kPa and 2.7 kPa, respectively, compared with water.